2015
DOI: 10.1089/ars.2014.6189
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Mediated Suberoylanilide Hydroxamic Acid Sensitivity in Breast Cancer

Abstract: Aims: Vorinostat (suberoylanilide hydroxamic acid; SAHA) is a histone deacetylase inhibitor (HDACi) approved in the clinics for the treatment of T-cell lymphoma and with the potential to be effective also in breast cancer. We investigated the responsiveness to SAHA in human breast primary tumors and cancer cell lines. Results: We observed a differential response to drug treatment in both human breast primary tumors and cancer cell lines. Gene expression analysis of the breast cancer cell lines revealed that ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 78 publications
1
3
0
Order By: Relevance
“…SAHA inhibits the class I HDACs (HDAC1, HDAC2, HDAC3) and the class II HDACs (HDAC6) and under the trade name Zolinza® was the first histone deacetylase inhibitor approved by FDA for clinical use in cutaneous T cell lymphoma (CTCL) 31, 32. SAHA is a compound with low toxicity in normal cells 33, which was also confirmed in the current study, and high therapeutic potential for different tumors including colon cancer 34, prostate cancer 35, breast cancer 36, non-small cell lung cancer 37, pancreatic cancer 38, glioma cells 39, uterine sarcoma 40, ovarian cancer 41 and oral squamous cell carcinoma 42. In the present study, we showed that SAHA suppressed the growth of larynx cancer cell lines at micromolar concentrations in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 75%
“…SAHA inhibits the class I HDACs (HDAC1, HDAC2, HDAC3) and the class II HDACs (HDAC6) and under the trade name Zolinza® was the first histone deacetylase inhibitor approved by FDA for clinical use in cutaneous T cell lymphoma (CTCL) 31, 32. SAHA is a compound with low toxicity in normal cells 33, which was also confirmed in the current study, and high therapeutic potential for different tumors including colon cancer 34, prostate cancer 35, breast cancer 36, non-small cell lung cancer 37, pancreatic cancer 38, glioma cells 39, uterine sarcoma 40, ovarian cancer 41 and oral squamous cell carcinoma 42. In the present study, we showed that SAHA suppressed the growth of larynx cancer cell lines at micromolar concentrations in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 75%
“…As previously illustrated, ROS are considered critical players in anoikis -resistance due to their positive effect on pro-survival cell signaling and tumor metastasis [ 60 ]. However excessive and unmitigated ROS increase can result in cell death [ 102 , 103 , 104 ]. Remarkably, our results indicated that the antioxidant NAC can partially rescue H89-treated detached cells, underscoring the fact the PKA controls an antioxidant response critical for anoikis -resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Suberoylanilide hydroxamic acid (SAHA), also called vorinostat, belongs to the hydroxamic acid class of histone deacetylase (HDAC) inhibitors 7 , 8 . It was shown that SAHA exerted great clinical utility as a therapeutic intervention after intracerebral hemorrhage 9 .…”
Section: Introductionmentioning
confidence: 99%